LOXODROMES ON CANAL SURFACES IN EUCLIDEAN 3-SPACE - Babaarslan, Murat (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
We obtain the differential equations of loxodromes on canal surfaces which cut all meridians or parallels at a constant angle in the Euclidean 3-space. Also we compute the arc-lengths of loxodromes and give some examples by using Mathematica to illustrate our results.